Trust and Security In Financial Technology: How Much Does It Matter? - Poudel, Omkar; Acharya, Pradeep (International Research Journal of MMC, 2023)
With the increase use of Fin-tech and increasing number of cashless transaction, the world is moving towards the digital revolution where people are using lesser amount of physical cash with every passage of time. With the increase of Fin-tech various issues related to security, risk, trusts are also in the increasing trend. Keeping this in mind, the purpose of the study is to examine the security factor and its impact on usage intention. At the same time the study examines the mediating role of trust between security of Fin-tech and usage intention. Data from 223 Fin-tech users have been collected via an online survey. The partial least square structural equation modeling (PLS-SEM) approach is then used to assess this data. The data and analysis showed that there is a substantial positive relationship between usage intention and security concerns with regard to fin-tech, and that trust partially mediates this relationship.